Parenting Islami dalam membentuk karakter anak: Strategi efektif parenting Islami untuk generasi penerus - Kirana, Ayu Cendana Cendana (Maliki Interdisciplinary Journal, 2024)
This journal article evaluates the comparison between Islamic parenting and authoritarian parenting to assess the impact of these two approaches on child development. The background of this research highlights the importance of understanding the effects of parenting methods on the psychological, social, and academic aspects of children. This study employs a descriptive analysis method based on the collection of theories and references from the internet. The research approach is focused on content analysis of various theories and information found online. The results indicate that Islamic parenting, which integrates religious values and emotional involvement, tends to produce children with better psychological well-being and positive social relationships. Conversely, authoritarian parenting, characterized by strict control and limited emotional interaction, can contribute to negative impacts on child development. These findings contribute to a deeper understanding of the importance of the Islamic approach in shaping a healthy and competitive generation.